The impact of the internet and its applications on radio audiences - Al-hjouj, Mohammad Mubarak (Journal of Humanities & Social Sciences, 2020)
The study aimed to identify the effects faced by radio from new technologies and applications that have been able to attract a lot of audience traditional media, especially radio. To achieve this goal descriptive approach used methods, a tactic survey the public media, using the tool questionnaire, and then applied on a random sample of the Jordanian public in order to stand on their attitudes towards the Internet and its applications on the effects of listening to the radio. The study proved that the Internet and its applications impacted adversely on listening to the radio, where the ratio came from listening to the Jordanian public 39% versus 61% for to the radio. The study showed that the most important reasons for the Jordanian public to listen to radio stations is to satisfy recreational, cultural and scientific desires, and love of the Jordanian public to some of the broadcasters who provide programs and radio stations will help to know what is going on from the events. The study showed that there is dissatisfaction by the Jordanian public about the programs offered by the radio, where he said that 55% of the study sample who listen to the radio. From these results will be achieved hypotheses and the study of the theory relied on by the study and followed the approach uses the theory. The study recommends the importance of working to improve the quality of programs offered by the radio and to the satisfaction of listeners, and to increase the broadcast hours of programs that attract public radio institutions. Reconnaissance work ray studies to the public periodically to learn about their needs and desires. Supplying radio institutions modern techniques that would maintain the audience, and supplement her human cadres qualified and capable of using communication technology and increased awareness among workers about the concept of communication technology to the technique of active impact on the performance of radio stations, and set up special centers set the media production enterprise quality media. The study recommends researchers to conduct further research and studies for the radio service and support for its survival in the media arena.